OESOPHAGEAL CANCER IN NORTHERN AREAS OF PAKISTAN - Ali, Anwar; Naseem, Muhammad; Khan, Taj Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Oesophageal carcinoma is the leading cause of death from cancers. Most of the oesophageal carcinomas are either squamous cell carcinomas or adeno-carcinomas. The cervical oesophagus is an uncommon site of the disease. There is an increase of 15-20 percent mortality rate over the past two to three decades, during which time the histologic pattern of the disease has also changed significantly. Objective: The objective of this study was to see the incidence of oesophageal carcinoma in different sex and age groups, in the Northern Areas of Pakistan. Method: This was a retrospective study over a period of 7 years which was designed to assess age and sex incidence for oesophageal carcinoma in Northern Areas of Pakistan. A total of 69 already diagnosed carcinomas of the oesophagus were included in the study, all these cases were from Malakand Division of Northern Pakistan. All specimens were stained and examined microscopy. The demography of the disease and type of carcinoma were evaluated. Results: Out of 69 diagnosed cases of oesophageal carcinomas, squamous cell carcinoma was the found in 64 (92.5%) while adenocarcinoma was seen in 5 (7.5%) cases. Out of 64 squamous cell carcinomas, moderately differentiated carcinomas were the most common 34 (49.2%). Conclusion: Most of the oesophageal carcinomas were squamous cell carcinomas and were mostly biopsied from the lower 1/3rd of the oesophagus. The mean age of patients was 42 years in males (M) and 53 years in females (F). F:M was 1:3. All patient presented in advanced stage with dysphagic symptoms. No in situ or mucosal carcinoma was identified in this study. Radiological assessment also showed late stages of the disease. Keyword: Oesophageal carcinoma, incidence, type, demography